Toward a Common Research Model: Leveraging Education Abroad Participation to Enhance College Graduation Rates. (May 2018) - Haupt, John; Ogden, Anthony C.; Rubin, Donald
This article calls for a common research model that can be replicated across institutions to systematically collect data on the impact of education abroad participation on college graduation rates. The ultimate goal of the proposed GRAD LEAP (Leveraging Education Abroad Participation for Graduation) model is to facilitate a meta-analysis yielding generalizable findings that can inform both institutional and national education abroad policy. The model consists of two levels of analysis: (a) a descriptive analysis to estimate and compare true graduation rates for education abroad participants and nonparticipants, and (b) a parametric analysis to estimate the value-added of education abroad participation, beyond factors already understood to impact graduation rates. The proposed research model can be expanded to include analysis of the impact of specific program factors on graduation rates (e.g., program duration, program type, student accommodation, etc.).